Alterations of the default mode network, salience network, and frontoparietal network in non-problematic Internet use and their association with mood regulation: from an internet literacy perspective - Shibata, Mami; Tsurumi, Kosuke; Kobayashi, Kei; Yoshimura, Sayaka; Spantios, Michael; Oishi, Naoya; Murai, Toshiya; Fujiwara, Hironobu (Frontiers in Neuroscience, 2025)
IntroductionAlthough a number of neuroimaging studies on problematic internet use (PIU) have been conducted, few studies on non-problematic internet use (non-PIU) are available; therefore, the influences of non-PIU on brain function are unclear. Resting-state functional connectivity (rsFC) could be an appropriate tool to investigate subclinical samples, such as non-PIU, to capture the potentially subtle changes compared to clinical samples. In the context of rsFC, the default mode network (DMN), the central executive network (CEN), and the salience network (SN) are representative of the brain networks. Because accumulating studies have investigated rsFC between these networks in PIU samples, investigating rsFC between these networks in non-PIU samples could give us a clue to elucidate the neural basis of non-PIU in relation to those of PIU.MethodsWe recruited 119 healthy volunteers and used the General Problematic Internet Use Scale-2 (GPIUS-2) to measure their propensity to use the Internet. The GPIUS-2 consists of four subscales. We analyzed the correlation between the degree of Internet use assessed by the GPIUS-2 and the rsFC of the regions comprising DMN, CEN, and SN using resting-state functional magnetic resonance imaging in non-PIU samples.ResultsThere was a positive correlation between the mood regulation subscale score and SN (bilateral anterior insula) – CEN (left lateral prefrontal cortex: LPFC), SN (left anterior insula) – DMN (medial prefrontal cortex: MPFC), and DMN (MPFC) – CEN (right LPFC) rsFC. Additionally, there was a negative correlation between the mood regulation subscale score and DMN – FPN rsFC.DiscussionThe correlations between rsFC and non-PIU suggest that non-PIU and PIU could influence rsFC in opposite directions. Furthermore, the hub regions comprising connections correlated with non-PIU in this study are involved in cognitive and emotional processes. One possible interpretation would be that the bilateral insula and synchronized LPFC activity in individuals with non-PIU results in well-functioning emotion regulation as an appropriate coping strategy, in contrast to PIU. These findings suggest that non-PIU might contribute to health promotion through mood regulation with alterations in the functional connectivity between the regions involved in mood regulation.